1994
DOI: 10.1149/1.2055027
|View full text |Cite|
|
Sign up to set email alerts
|

Ionic Conductivity in Ordered and Disordered Phases of Plastic Crystals

Abstract: Pentaglycerine (PG) and tris-hydroxy-aminomethane (Tris) are potential thermal energy storage materials which undergo energetic solid-state phase transformations. The low temperature a-phase structure of PG is body-centered tetragonal and that of Tris is orthorhombic. The high-temperature phase structure of both compounds is face-centered cubic. Polymorphic changes in the structure occur at 89~ for PG and 135~ for Tris. These compounds are dielectrics at low temperature with conductivities on the order of i0 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Even in the pure sample, the shape of the transition is asymmetric [22]. Chandra et al, and Smith et al, based on a study of pentaerythritol, have proposed that the α → γ order-disorder transition is responsible for this thermal event [20,21]. This transition apparently involves the rearrangement of the -OH groups via rotation about the C-C axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the pure sample, the shape of the transition is asymmetric [22]. Chandra et al, and Smith et al, based on a study of pentaerythritol, have proposed that the α → γ order-disorder transition is responsible for this thermal event [20,21]. This transition apparently involves the rearrangement of the -OH groups via rotation about the C-C axis.…”
Section: Resultsmentioning
confidence: 99%
“…1) contains several hydroxyl groups which one would envisage could lead to better compatibility with acid dopants and potentially offers alternative sites for the proton to reside and migrate between. Pure pentaglycerine has been studied by Chandra et al [20] and was shown to have a solid-solid phase transition from an ordered crystalline phase to a disordered plastic crystal phase at 85°C and a melting point at approximately 200°C. In the pure state, the ionic conductivity should be negligible, although Chandra was able to measure a value of 1.34 × 10 − 6 S/cm, at 105°C, apparently in the plastic phase, which may be attributed to impurities or alternatively, H + transport via the hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…The conformational characteristics of plastic crystals lead to many interesting physical and chemical properties. These properties may be potentially exploited in applications such as thermal energy storage 2,5,6 and as solid electrolytes. 1,[7][8][9][10] Organic ionic plastic crystals (OIPCs) are a more recently developed subclass of plastic crystal that display specific fast-ion transport capability, where dopant ions (such as Li + ) are highly mobile in an OIPC matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These materials typically display one or more solid-solid phase transitions, from a fully ordered crystalline phase at low temperatures to a disordered, plastic phase. 16,17 One source of the disorder at the molecular level is the presence of rotational motion of the molecule on its lattice site, giving rise to what are known as rotator phases. 18,19 In the ionic compounds, the rotator motions can involve either the cation or the anion or both, and it is these that become progressively activated in the higher temperature phases.…”
Section: Introductionmentioning
confidence: 99%